Designing Powtoon-Mediated Interactive Multimedia to Leverage Students’ Learning Behavior in the Qur’an and Hadith - Arbain Nurdin (Faculty of Education and Teacher Training, Institut Agama Islam Negeri Pekalongan, 2020)
The present study aims to describe the process of development, quality, assessment, and students’ learning behavior toward Powtoon-mediated interactive multimedia for the Qur’an and Hadith. Grounded in R&D (Research and Development), data were garnered through validation, questionnaire, as well as observation. The collected data then were analyzed by using content analysis and descriptive analysis. Study findings expose that first, the stages of interactive multimedia design included identifying the potential and problems of learning the Qur’an and Hadith, collecting the lesson material of the Qur’an and Hadith for seventh graders of junior secondary school, designing products based on learning objectives, having the design validated by experts, revising the design on expert recommendations, managing a product trial on a small group, revising products, and carrying out a product trial on a large group. Second, the first assessment of the teaching media expert was considered good (82%), and the second one was considered very good (92%). Meanwhile, the first assessment of the teaching material expert was considered good enough (70%), and the second one was considered very good (90%). Lastly, the assessment of both small and large group was considered good. The study contributes to novel practical insights on the design of Powtoon-featured interactive multimedia as an endeavor to foster the students’ learning behavior in the material. This study also demonstrates that the student learning behavior was leveraged, particularly in the aspects of attitudes, habits, as well as learning interest.